ANALISIS STRUKTUR RETORIKA BAGIAN HASIL DAN PEMBAHASAN ARTIKEL JURNAL BIDANG BERBAHASA INDONESIA BIDANG ILMU SASTRA PADA JURNAL “BISA” FKIP UNIVERSITAS BENGKULU - Atmaja, Hary (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
This study was to describe the structure of rhetoric and linguistic characteristics of a part of results and discussion of articles in Indonesian language research journals in the field of literary studies. This research uses descriptive method. Data and sources of data in this study are the following documents speech writer in the text, while the data source in the form of 30 research journal articles in the field of research literature. Rhetorical structure analysis using the theory Swales which consists of 8 stages. Sedangkan ciri linguistik menggunakan teori (Wilujeng 2007, Ba?dulu 2004 dan Alwi, dkk., 2003) consisting of, among others; active voice, passive sentences and conjunctions. The results of the study of rhetoric structural analysis and discussion section of the results of research in the field of science research AJP literary form of the use of the stages are found or used. The results of the most common stages of research journal articles (AJP) Indonesian language literature on the science research journal “BISA” ie the first stage, (information about the study), the second stage (statement about the study results), and fifth stages (A description of the research results). While the linguistic characteristics contained in section AJP results and discussion in the field of literature the most dominant research that active use of cohesion grammatical sentence reference , conjunction and lexical cohesion markers reps in the research journal articles ( BISA ) section of the results and discussion of science research literature.